Dual-Specificity Phosphatases and Kidney Diseases - Haiyang Li (Karger Publishers, 2021)
Background: Dual-specificity phosphatases (DUSPs) belong to the family of protein tyrosine phosphatases, which can dephosphorylate both serine/threonine and tyrosine residues. During the past decades, DUSPs have been implicated in various physiological and pathological activities. Besides mitogen-activated protein kinases (MAPKs) as the main substrates, other protein and nonprotein substrates can also be dephosphorylated by DUSPs. Aberrant regulations of DUSPs have been found in various diseases such as cancer, neurological disorders, and kidney diseases, suggesting the involvement of DUSPs in the pathogenesis of diseases. Summary: In this review, we summarize the general characteristics of DUSPs and the research progress made in the field of kidney diseases, including diabetic nephropathy, hypertensive nephropathy, chronic kidney disease, acute kidney injury, and lupus nephritis. As the main biochemical function of DUSPs is to dephosphorylate MAPKs activity, decreased DUSPs are found in kidney disease models, whereas forced DUSPs expression reverses the disease presentation, which was proved by using transgenic or gene knockout model. Key Messages: Mounting evidence demonstrates that DUSPs have essential physiological and pathological functions in kidney disease. Fully understanding the functions and mechanisms of DUSPs in kidney disease contributes to their clinical application in translation medicine.